2020
DOI: 10.1111/1346-8138.15517
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, trichoscopy, histopathology and treatment outcomes of frontal fibrosing alopecia in an Asian population: A retro‐prospective cohort study

Abstract: Frontal fibrosing alopecia (FFA) is a distinctive lymphocytic scarring alopecia with rapid increase in prevalence. Most FFA series are retrospectively reported from Caucasians with only few from Asians. The objective of this study was to characterize the clinical, trichoscopic and histopathological findings as well as treatment outcomes. This was a retro‐prospective cohort study of patients diagnosed with FFA from 1 January 2010 to 1 November 2019. All patients were asked to present for re‐examination. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…The hairline recession in FFA and the frequent concomitant androgenetic alopecia (AGA) that occurs in patients with LPP and FFA have led some authors to propose a role for androgen excess in FFA, largely on the basis of the postmenopausal predominance of affected females ( Dawn et al., 2003 ; Ranasinghe et al., 2017 ). Although definitive evidence for this hypothesis is missing, reports of clinical benefits seen in some patients treated with 5α-reductase inhibitors (5ARIs) such as dutasteride ( Jerjen et al., 2021 ; Lobato-Berezo et al., 2018 ; Panchaprateep et al., 2020 ; Pindado-Ortega et al., 2021 ; Vañó-Galván et al., 2016 ) have been interpreted as supporting it. However, the results of retrospective cohort studies of moderate quality where patients were treated with concomitant therapies in addition to 5ARIs and/or serum androgen and estrogen levels were not measured should be interpreted cautiously ( Murad and Bergfeld, 2021 ).…”
Section: Other Factorsmentioning
confidence: 99%
“…The hairline recession in FFA and the frequent concomitant androgenetic alopecia (AGA) that occurs in patients with LPP and FFA have led some authors to propose a role for androgen excess in FFA, largely on the basis of the postmenopausal predominance of affected females ( Dawn et al., 2003 ; Ranasinghe et al., 2017 ). Although definitive evidence for this hypothesis is missing, reports of clinical benefits seen in some patients treated with 5α-reductase inhibitors (5ARIs) such as dutasteride ( Jerjen et al., 2021 ; Lobato-Berezo et al., 2018 ; Panchaprateep et al., 2020 ; Pindado-Ortega et al., 2021 ; Vañó-Galván et al., 2016 ) have been interpreted as supporting it. However, the results of retrospective cohort studies of moderate quality where patients were treated with concomitant therapies in addition to 5ARIs and/or serum androgen and estrogen levels were not measured should be interpreted cautiously ( Murad and Bergfeld, 2021 ).…”
Section: Other Factorsmentioning
confidence: 99%
“…Regarding the human race, FFA has been described worldwide, although most cases have been reported in European and North American countries, mainly among Caucasians and fewer among black-skinned populations [ 16 ], whereas only a few cases have been reported in Asia, where the incidence may be lower [ 21 , 22 , 23 , 24 ]. Indeed, a recent study regarding the prevalence of FFA and LPP in New York City observed that the prevalence of the combined group LPP/FFA was highest among non-Hispanic Caucasians (0.091%) [ 6 ].…”
Section: Epidemiology and Demographic Datamentioning
confidence: 99%
“…LPPigm may be associated to FFA, mainly in dark skin types, such as Hispanic/Latino and black-skinned patients (44–54%) [ 24 , 69 ], as well as Asians [ 24 ]. It appears as brown to grey macular pigmentation mostly on the face and neck, but also in flexural areas [ 15 , 68 , 138 ].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…1,2 It is most commonly seen in postmenopausal women, [3][4][5][6][7][8] but it has also been observed in premenopausal women [4][5][6][7] and men. 5,9,10 While the majority of the reported patients have been of European descent, FFA has also occurred in black 5,8,11,12 and Asian patients 13,14 from various nations. The incidence of FFA is unknown, but the number of women seeking diagnosis and help for this condition has markedly increased in recent years, currently representing the majority of new cases of cicatricial alopecia.…”
Section: Introductionmentioning
confidence: 99%